Linear and spatial dimensions of the frontal sinuses of mature persons according to computed tomography - Vasyliv , M.-A.L. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Among all the paranasal sinuses, the frontal sinuses occupy a special place, which is caused, in particular, by the significant variability of their shape, size, and topography. Numerous studies are devoted to the study of the peculiarities of their establishment, development and structure during different age periods of ontogenesis. The purpose of our study was to find out the regularities of the ratio of linear and spatial dimensions of the frontal sinuses of people of different sexes in different periods of adulthood. Methods. The study was carried out by processing 40 series of anonymized computed tomograms of adults from the archive of the Lithotripsy Center (Lviv). The randomized sample of processed materials included CT series of 20 men and 20 women, 10 people in each age groups under 35 years and after 35 years. All examined persons had no pathological changes and injuries that was diagnosed or detected during the examination of nose area and frontal bone. The examination was carried out on the Siemens SOMATOM GO.UP 32 (64) device. Determination of frontal sinus volumes was performed in the software application Vidar Dicom Viewer in the version dated 08/12/2022. Statistical calculations were performed by using software BioStat LE 7.6.5 and IBM SPSS Statistics 21. Their results are presented as Me (25%; 75%), where Me is the median, 25% is the 25th percentile (first quartile), 75 % – 75th percentile (third quartile). The difference between groups was considered significant at p<0.05. Results. It was established that all studied linear dimensions in men are larger than in women. The dimensions of the frontal sinuses in men and women of both age groups are characterized by pronounced asymmetry, the exception is the depth of the sinuses in women, in particular - after 35 years. The volumes of the frontal sinuses in men are significantly larger than in women, with the exception of the left sinuses in the group under 35 years of age. In men, the age-related dynamics of the volume of the frontal sinuses coincides with the dynamics of their width on the right, and with the dynamics of height, width and depth on the left. In women, the age-related dynamics of the volume of the frontal sinuses on the right coincides with the dynamics of their width, and on the left - their depth. Conclusion. The linear dimensions and volume of the frontal sinuses in men and women of different periods of adulthood are characterized by significant variability and require further study to clarify the patterns of their age dynamics.